LITERATUR REWIEW: INISIASI MENYUSU DINI DAN ASI EKSLUSIF SEBAGAI PERCEPATAN PENURUNAN STUNTING: LITERATUR REWIEW: INISIASI MENYUSU DINI DAN ASI EKSLUSIF SEBAGAI PERCEPATAN PENURUNAN STUNTING - Agnis Sabat Kristiana; Diana Noor Fatmawati; Dian Samtyaningsih; Afrihal Afiif Ibaadilah (Poltekkes Kemenkes Malang, 2021)
Children are unique figures with different stages of growth and development. The period of child development is stunting. The prevalence of stunting in Indonesia is from 37.2% in 2013 to 30.8% in 2018. One of the stunting interventions is the initiation of early breastfeeding by giving breast milk or colostrum and encouraging exclusive breastfeeding. The purpose of this literature review is to analyze early initiation of breastfeeding and exclusive breastfeeding as an acceleration of stunting reduction. Search articles using databases on Google Scholar, Garuda Portal and Pubmed. There were 7 articles that met the inclusion criteria. The results of a literature review of 7 research journals stated that there was a relationship between IMD and exclusive breastfeeding with stunting. Therefore, to accelerate the reduction of stunting, it is necessary to increase the provision of IMD and exclusive breastfeeding to infants aged 0-6 months with methods that are in accordance with standards. Keywords: Early Initiation of Breastfeeding, Exclusive Breastfeeding, Stunting